Genome-wide inbreeding estimation within Lebanese communities using SNP arrays - Jalkh, Nadine (Eur J Hum Genet, 2015)
Consanguineous marriages have been widely practiced in several global communities with varying rates depending on religion, culture, and geography. In consanguineous marriages, parents pass to their children autozygous segments known as homozygous by descent segments. In this study, single-nucleotide polymorphisms were analyzed in 165 unrelated Lebanese people from Greek Orthodox, Maronite, Shiite and Sunni communities. Runs of homozygosity, total inbreeding levels, remote consanguinity, and population admixture and structure were estimated. The inbreeding coefficient value was estimated to be 1.61% in offspring of unrelated parents over three generations and 8.33% in offspring of first cousins. From these values, remote consanguinity values, resulting from genetic drift or recurrent consanguineous unions, were estimated in offspring of unrelated and first-cousin parents to be 0.61 and 1.2%, respectively. This remote consanguinity value suggests that for any unrelated marriages in Lebanon, the mates could be related as third cousins or as second cousins once removed. Under the assumption that 25% of marriages occur between first cousins, the mean inbreeding value of 2.3% may explain the increased incidence of recessive disease in offspring. Our analysis reveals a common ancestral population in the four Lebanese communities we studied.